Application of the Ex Aequo Et Bono Principle to the Reconsidered Arbitration Award (Case Study of the Decision of the Indonesian National Arbitration Board (BANI) NUMBER 43032/VI/ARB-BANI/2020) - Irgi Fahreza Chandra; Syofiaty Lubis (Dinasti Research, 2024)
In business cooperation agreements, it is important to establish measures to prevent future conflicts. This involves adding a